The Influence of Work Discipline and Work Motivation on the Work Productivity of Computer Stitching Employees at PT Adis Dimension Footwear, Tangerang Regency - Ramdan, Muhamad Sahrul; Fahmi, Khaeru (Faculty of Science and Technology University of Pramita Indonesia, 2026)
The purpose of this study was to determine how much influence work discipline and work motivation simultaneously have a significant effect on the work productivity of employees in the Computer Stitching section at PT Adis Dimension Footwear, Tangerang Regency.This study uses a quantitative descriptive method. The research sample consisted of 80 respondents. The technique used to determine the sample in this study was the simple random sampling technique. The results of this study indicate that (1) partially, work discipline significantly influences employee performance in the Computer stitching section at PT. Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value> t table (6.641> 1.991) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, work motivation significantly influences employee performance in the Computer stitching section at PT. Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value> t table (5.786> 1.991) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, human resource development and work motivation significantly influence employee performance in the Computer Stitching section at PT. Adis Dimension Footwear, Tangerang Regency, as indicated by Fcount> Ftable (97.882>3.15) with a significance level of 0.000, thus Ha is accepted and H0 is rejected.Based on the results of the study, it can be concluded that the variables of human resource development and work motivation, both partially and simultaneously, have a significant influence on employee performance in the Computer Stitching section at PT. Adis Dimension Footwear, Tangerang Regency.